2019
DOI: 10.1111/bju.14737
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound guidance can be used safely for renal tract dilatation during percutaneous nephrolithotomy

Abstract: ObjectivesTo compare clinical outcomes in patients who underwent percutaneous nephrolithotomy (PCNL) with renal tract dilatation performed under fluoroscopic guidance vs renal tract dilatation with ultrasound guidance. Patients and MethodsWe conducted a prospective observational cohort study, enrolling successive patients undergoing PCNL between July 2015 and March 2018. Included in this retrospective analysis were cases where the renal puncture was successfully obtained with ultrasound guidance. Cases were th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 32 publications
(40 reference statements)
0
22
0
Order By: Relevance
“…In one study with 138 subjects, totally ultrasound-guided balloon dilation was achieved in 131 (94.9%), and the remaining 7 (5.1%) cases required a switch to fluoroscopy (17). In another study with 207 cases undergoing ultrasoundguided balloon dilation, the success rate of tract dilation on the first attempt was 88.4% (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In one study with 138 subjects, totally ultrasound-guided balloon dilation was achieved in 131 (94.9%), and the remaining 7 (5.1%) cases required a switch to fluoroscopy (17). In another study with 207 cases undergoing ultrasoundguided balloon dilation, the success rate of tract dilation on the first attempt was 88.4% (11).…”
Section: Discussionmentioning
confidence: 99%
“…A few authors reported their technique of ultrasound monitoring the dilation process, including balloon dilator (11,17), serial Amplatz dilators(9), one-shot Amplatz dilators (18), or telescopic metal (Alken) dilators (19). Among these dilators, balloon has been widely used in ultrasound-guided PCNL and has been considered relatively easier to apply under ultrasound guidance (12).…”
Section: Discussionmentioning
confidence: 99%
“…As urologists, we should all be aware of these risks and follow the ALARA (As Low As Reasonably Achievable) principals of keeping doses to a minimum. Thus, this paper is particularly welcome and shows zero‐radiation procedures can be safely performed. The authors now attempt this technique for all PCNL procedures and achieve US‐only puncture and dilatation in over half of their patients.…”
mentioning
confidence: 89%
“…In this month’s BJUI , Armas‐Phan et al report on a prospective observational trial of fluoroscopic vs ultrasound (US)‐guided tract dilatation during percutaneous nephrolithotomy (PCNL). A total of 176 patients underwent successful initial US‐only guided puncture; of these patients, 138 had US‐only dilatation, while in 38 fluoroscopy was required.…”
mentioning
confidence: 99%
“…Although thought to be less invasive than open or laparoscopic stone removal, surgeons are sometimes reluctant to proceed with PCNL due to complications related to renal access (7). A variety of renal access methods, such as ultrasound guidance (8) and miniaturized tract, possibly with the utilization of a flexible nephro-or ureteroscope (9), could mitigate the major unique complications of PCNL without reducing its efficacy for stone removal. While the European Association of Urology (EAU) (10) and the Urological Association of Asia (UAA) (11) guidelines suggest that antegrade ureterolithotripsy (URSL) may be a good alternative for the treatment of proximal ureteral stones larger than 10 mm, there is still a lack of evidence on the optimal case for the application of antegrade URSL over retrograde URSL in real practice.…”
Section: Original Articlementioning
confidence: 99%